Mesenchymal stromal cells for treatment of the acute respiratory distress syndrome: The beginning of the story. (November 2015) - Morrison, T; McAuley, DF; Krasnodembskaya, A
In spite of decades of research, the acute respiratory distress syndrome (ARDS) continues to have an unacceptably high mortality and morbidity. Mesenchymal stromal cells (MSCs) present a promising candidate for the treatment of this condition and have demonstrated benefit in preclinical models. MSCs, which are a topic of growing interest in many inflammatory disorders, have already progressed to early phase clinical trials in ARDS. While a number of their mechanisms of effect have been elucidated, a better understanding of the complex actions of these cells may pave the way for MSC modifications, which might enable more effective translation into clinical practice.